Smart City Construction and Urban Green Development: An Analysis from the Perspectives of Industrial Structure and Technological Progress - Zhang, Diandian; Wu, Haiqiao (Urban Planning and Construction, 2025)
As an innovative urban development model, smart cities have become a pivotal strategy for fostering green, efficient, and sustainable urban growth, epitomizing efficiency, intelligence, and sustainability. Investigating the impact of the smart city pilot policy on urban green development not only deepens our understanding of smart city construction but also further supports urban green development. This study utilizes panel data from 191 Chinese cities (2008-2022) and employs a DID model and a mediating effect model to analyze the influence of smart city construction on urban green development. The smart city pilot policy significantly and positively impacts urban green development, a finding that remains robust across various tests. The direct influence of the smart city pilot policy on urban green development is seen in three key areas: resources, environment, and technology. Mechanism tests indicate that the smart city pilot policy promotes urban green development via two primary pathways: industrial structure upgrading and technological progress. The impact shows clear heterogeneity, having a significant effect on non-resource-based cities and small cities. The study proposes several policy recommendations, including promoting the digitalization and informatization level of industries, strengthening the guidance and regulation of smart city construction and technological innovation, and establishing a regional coordination mechanism.